Heavy metal concentration in the fish channa obscura from alaro Stream in Ibadan, Nigeria (2014)
The heavy metal concentration in the fish Channa obscura from Alaro Stream in Ibadan was assessed. Twenty-seven fish (C.obscura) were collected between January and December 2003 (Dry and rainy season).Muscle, liver, bone, gills, gut and fins of the fish were analyzed for cadmium (Cd) and lead (Pb) using the inductively coupled plasma- mass spectrometer (ICP-MS).Quality assurance of the results was obtained through the use of bovine liver as a standard reference material (SRM) from the National Institute of Standards and Technology (NIST). The range of the Cd in the organs of C. obscura was 0.000- 0.507ppm, with the highest mean concentration in the gut (0.500ppm) and the lowest in the bones (0.057ppm). The order of mean increment in the Cd concentration was: bone<muscle<gills<liver<fins<gut. The range of Pb in the organs of C. obscura was 0.000-5.850ppm with the highest mean concentration in the liver (3.32ppm) and the lowest in the bone (1.53ppm).The order of mean increment of Pb in the organs was: bone<muscle<fins<gills<gut <liver. This study shows that mean concentration of the heavy metals Cd and Pb in the organs of C. obscura from Alaro stream in Ibadan exceeded the World Health Organization (WHO) guideline limits set for them. This means that Alaro stream is polluted and fish such as C. obscura caught from the stream is unfit for human consumption due to the public health consequences posed in consuming such fish. A biomonitoring program for heavy metals in aquatic ecosystems is therefore recommended